2016
DOI: 10.1177/0973408216661442
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of Education for Sustainable Development (ESD) to Quality Education: A Synthesis of Research

Abstract: This research is a synthesis of studies carried out in 18 countries to identify contributions of education for sustainable development (ESD) to quality education. Five common questions were used for the interviews in each country to solicit education leaders and practitioners’ views on the outcome and implementation of ESD. The analysis revealed that major themes repeated across the 18 studies, showing that ESD contributes in many ways to quality education in primary and secondary schools. Teaching and learnin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
161
0
20

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 293 publications
(257 citation statements)
references
References 7 publications
2
161
0
20
Order By: Relevance
“…Participants valued such an integration because they thought it could develop their reflective thinking skills and benefit their language learning process. This finding lends support to previous research that reported the development of students' cognitive knowledge and reflective thinking skills in similar practice [51].…”
Section: Discussionsupporting
confidence: 90%
“…Participants valued such an integration because they thought it could develop their reflective thinking skills and benefit their language learning process. This finding lends support to previous research that reported the development of students' cognitive knowledge and reflective thinking skills in similar practice [51].…”
Section: Discussionsupporting
confidence: 90%
“…In an international comparative study, Laurie et al (2016) stated that ESD was best implemented when issues were addressed in multidisciplinary ways and across curricula. When collaborating on interdisciplinary projects, multidisciplinary approaches enable teachers to learn about curriculum content in areas outside of their specialty.…”
Section: Resultsmentioning
confidence: 99%
“…This reflects the fact that most of the Japanese ESD schools are primary, and so many of the study topics and materials that they select are from their school district and local area, which is the most meaningful geographical frame for young children. Laurie, Tarumi, McKeown, and Hopkins (2016) carried out studies in 18 countries to identify contribution of ESD to high-quality education. One main question posed by their research was, ìHow can ESD promote innovation in the teachingñlearning conceptual framework?î…”
Section: Local Esd Studymentioning
confidence: 99%
“…Hedefalk et al 2014), primary education (e.g. Green and Sommerville 2015;Laurie et al 2016) and secondary education (e.g. Laurie et al 2016).…”
mentioning
confidence: 99%
“…Green and Sommerville 2015;Laurie et al 2016) and secondary education (e.g. Laurie et al 2016). The topic of sustainability in higher education even has its own journal, 1 which is entering its 19th volume in 2018, as well as an international handbook dedicated to it (Barth et al 2015).…”
mentioning
confidence: 99%